Sub-$10 sound card photogate variants - Gingl Zoltán (PHYSICS TEACHER, 2011)
Recently, a simple and very low-cost photogate has been shown by Horton as an efficient experimentation tool in physics education. The photogate connects to the microphone input of a personal computer, and free software can be used to visualize the light interruptions caused by a moving object such as a pendulum. Although the device works properly, there are further possibilities of improvement and similar alternatives also exist. The following brief review may help teachers to pick the one that best fits their needs and possibilities